A 120-year record of resilience to environmental change in brachiopods - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Global Change Biology, 2018)
Keywords: dept.egm; peer-reviewed

Thicker shells compensate extensive dissolution in brachiopods under future ocean acidification - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Environmental Science & Technology, 2019)
Keywords: dept.egm; peer-reviewed

Ocean acidification does not impact shell growth or repair of the Antarctic brachiopod Liothyrella uva (Broderip, 1833) - Cross, Emma L.; Peck, Lloyd S.; Harper, Elizabeth M. (Journal of Experimental Marine Biology and Ecology, 2015)
Marine calcifiers are amongst the most vulnerable organisms to ocean acidification due to reduction in the availability of carbonate ions for skeletal/shell deposition. However, there are limited long-term studies on the possible impacts of increased pCO2 on these taxa. A 7month CO2 perturbation experiment was performed on one of the most calcium carbonate dependent species, the Antarctic brachiopod Liothyrella uva, which inhabits the Southern Ocean where carbonate ion saturation levels are amongst the lowest on Earth. The effects of the predicted environmental conditions in 2050 and 2100 on the growth rate and ability to repair shell in L. uva were tested with four treatments; a low temperature control (0°C, pH7.98), a pH control (2°C, pH8.05), mid-century scenario (2°C, pH7.75) and end-century scenario (2°C, pH7.54). Environmental change impacts on shell repair are rarely studied, but here repair was not affected by either acidified conditions or temperature. Growth rate was also not impacted by low pH. Elevated temperature did, however, increase growth rates. The ability of L. uva to continue, and even increase shell production in warmer and acidified seawater suggests that this species can acclimate to these combined stressors and generate suitable conditions for shell growth at the site of calcification.
Keywords: CO; Calcification; Carbonate saturation; Climate change; dept.egm; pH

No ocean acidification effects on shell growth and repair in the New Zealand brachiopod Calloria inconspicua (Sowerby, 1846) - Cross, Emma L.; Peck, Lloyd S.; Lamare, Miles D.; Harper, Elizabeth M. (ICES Journal of Marine Science, 2016)
Surface seawaters are becoming more acidic due to the absorption of rising anthropogenic CO2. Marine calcifiers are considered to be the most vulnerable organisms to ocean acidification due to the reduction in the availability of carbonate ions for shell or skeletal production. Rhychonelliform brachiopods are potentially one of the most calcium carbonate-dependent groups of marine organisms because of their large skeletal content. Little is known, however, about the effects of lowered pH on these taxa. A CO2 perturbation experiment was performed on the New Zealand terebratulide brachiopod Calloria inconspicua to investigate the effects of pH conditions predicted for 2050 and 2100 on the growth rate and ability to repair shell. Three treatments were used: an ambient pH control (pH 8.16), a mid-century scenario (pH 7.79), and an end-century scenario (pH 7.62). The ability to repair shell was not affected by acidified conditions with >80% of all damaged individuals at the start of the experiment completing shell repair after 12 weeks. Growth rates in undamaged individuals >3 mm in length were also not affected by lowered pH conditions, whereas undamaged individuals <3 mm grew faster at pH 7.62 than the control. The capability of C. inconspicua to continue shell production and repair under acidified conditions suggests that this species has a robust control over the calcification process, where suitable conditions at the site of calcification can be generated across a range of pH conditions.
Keywords: dept.egm; peer-reviewed